PERUBAHAN TUTUPAN HUTAN MANGROVE DI PANTAI TIMUR SUMATERA UTARA PERIODE 1977-2006 - Onrizal, Onrizal (Perhimpunan Biologi Indonesia, 2010)
ABSTRACTLand-cover change of mangrove forests at eastern coast of North Sumatra in Period 1977 to2006. Mangrove is one of the world?s threatened major tropical environments. Nevertheless,activities that contribute to this depletion continue. The main objectives of this research wereto analyze the land cover change of mangrove forests in eastern coastal of North Sumatrabased on previous inventory in period 1997 to 2006 and to acquire the factors of mangrovedisturbance in the areas. In fact, mangrove forest areas in eastern coastal of North Sumatradecreased 59.68% from 103,425 ha in 1977 to 41,700 ha in year 2006. Expansion of aquacultureponds and extraction of timber and fuel wood were most important factors of mangrove forestdegradation in the areas. Therefore, we need to rehabilitate the degraded mangrove forests inthe area both massively and systematically, and to prevent the remaining mangrove forestsfrom destruction activities.Keywords: mangroves, land-cover change, North Sumatra